THE EFFECT OF PERCEIVED PRICE AND PERCEIVED QUALITY ON PURCHASE INTENTION AT SHMILY CUPCAKES STORE MANADO - Tansil, Michell Jay; Tielung, Maria V.J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Cupcakes are an option that consumers are able to offer delights cupcakes, flavors that suit the tastes of consumers, and use quality ingredients. This is done so that all of the products offered will be a place both in the eyes of the public as consumers or potential consumers, because in choosing products is based on buying the interest that will affect the type, the taste of the product that is bought. Therefore, the pastries entrepreneur/ company are required to continue to make improvements, especially on the quality of its products. This research aim of the influence of perceived price and perceived quality on consumer purchase intention partially and simultaneously. This research used quantitative method. The analytical method used was multiple linear regression analysis. The data used in this research is primary data obtain through the questionnaire. The population of this reseacrh is the consumer of SHMILY Cupcakes in Manado. The samples taken are 100 respondents. This research concludes findings there is a significant effect of perceived price and perceived quality on consumer purchase intention simultaneously. But partially the effect of perceived quality on consumer purchase intention is more significant than the effect of perceived price on consumer purchase intention. The owner of SHMILY cupcakes store should more consider of quality than price since there is a significant effect of quality on purchase intention. Â  Keywords: perceive price, perceive quality, consumer purchase intention. Â